Training of dual band HT-based emergency communication tools on member of KTB BPBD, yogyakarta - Denny Hardiyanto; Samuel Kristiyana; Dyah Anggun Sartika; Irfan Ahmad; Israa Al_Barazanchi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Currently, the development of communication technology is very advanced with the presence of cellular and internet technology. However, when there is a public security disturbance and in an emergency situation, cellular communication devices are very dependent on electricity sources and pulses to communicate. Besides, if a natural disaster occurs, the power source will go out and the cellular provider BTS will not function. Radio communication can be used as an adequate alternative technology in dealing with emergencies. Radio communication can be established using simple equipment such as HT (Hand Transceiver), transmitting antennas and repeater stations to extend the communication range. The advantages of radio communication are that it is easier to implement, economical, and has a wide coverage. Therefore, the purpose of this community service activity is to improve skills in using emergency communication tools and provide an understanding of Standard Operating Procedures on how to communicate in an emergency situation. The target of this activity includes members of the National Disaster Relief Agency (BPBD) at Yogyakarta City. There are 2 activities, namely radio frequency regulation and skills workshops using emergency communication tools (HT). The result of this community service activity is that the participants are skilled in communicating using HT in times of emergency.